Taxonomy and lectotypification of Lepidagathis barberi (Acanthaceae), a steno-endemic species from Tamil Nadu, India - Gnanasekaran, Gunadayalan; Joy King, Anishkar Feroshwa; Arisdason, Wilson (Phytotaxa, 2020)
The taxonomy and lectotypification of Lepidagathis barberi, a steno-endemic species of Tamil Nadu, are discussed in detail here along with colour photograph of habit and close-up of a flowering-twig and a digital image of lectotype specimen.